Quo Vadis Legal Protection for Victims of Sexual Harassment on Campus - Chandra Sitorus, Jeremy (Lex Scientia Law Review, 2019)
Sexual assault on campus has recently received widespread and unprecedented public attention. Sexual assault on campus is an iceberg phenomenon, it can happen to both men and women, although women have a higher risk. This study aims to provide an overview of what is classified as sexual assault. The results of this study conclude that there are still many victims of sexual assault who choose to remain silent and do not demand justice because of the imbalance of power relations and the normalization of sexual assault on campus. As well as the lack of firmness on the part of the parties so that the perpetrators can continue their activities on campus and cause deep trauma and fear in the victims. In addition, campus fact-finding activities cornered victims who dared to demand justice. Campus intervention is important to destroy the culture of normalizing sexual assaults that occur on campus. Including educating students to understand the meaning of consensual sexual contact.